Is International Law Conducive To Preventing Looming Disasters?. (May 2016) - van Aaken, Anne
Abstract: Looming disasters mostly require collective action but international law is traditionally consent based. For a state to be bound by international law, it needs to have ratified a treaty (e.g. concerning climate change) or must be bound by customary international law. This horizontal form of cooperation makes the system sensitive to collective action problems (like free‐riding on global public good, overuse of commons, begging‐thy‐neighbor etc.). I explore the question of whether other forms of cooperation, e.g. cooperation through soft law or international organizations mitigate the problem and under what circumstances this might be so. Furthermore, international law design might need to take into account internal processes within states (breaking up the black box) as well as behavioral economic insights. The paper suggests some mechanisms to help states overcoming the cooperation problem with regard to looming disasters and highlights their limits as well. It submits that international lawyers need to look at all behavioral mechanisms of international law in order to understand how it can be designed and used to prevent looming disasters. Abstract : Although not all public good problems are looming disasters, many of them are, e.g. climate change, depletion of fisheries and biodiversity, infectious diseases, antibiotics resistance, hormone active chemicals leading to infertility of human beings as well as animals, water depletion, grave financial crises, desertification and asteroids, to name only a few. All those problems are transnational or global and thus require international cooperation.